Cadmium exposure induces endothelial dysfunction via disturbing lipid metabolism in human microvascular endothelial cells. Issue 5 (17th November 2020) - Liang, Hao; Yue, Rongchuan; Zhou, Chao; Liu, Mengyu; Yu, Xi; Lu, Shengzhong; Zeng, Jing; Yu, Zhengping; Zhou, Zhou; Hu, Houxiang
Abstract: Cadmium (Cd) is an occupational and environmental heavy metal pollutant derived from many sources that is linked to endothelial homeostasis. The endothelium is an important site of Cd deposition, while increasing evidence has revealed there is a close relationship between endothelial dysfunction and abnormal lipid metabolism. However, the effects of the alterations in lipid metabolism on endothelial cells (ECs) after Cd exposure still remain unclear. In our study, human microvascular endothelial cells (HMEC‐1) were exposed to 40‐μM Cd for 6, 12, or 24 h or 10‐, 20‐, or 40‐μM Cd for 24 h, respectively. The Cd exposure accelerated the decomposition of triglyceride (TG) and resulted in the accumulation of free fatty acids (FFAs). These changes stimulated cytotoxicity, impaired fatty acid oxidation (FAO), induced reactive oxygen species (ROS) generation, altered the mitochondrial membrane potential (MMP), and decreased the ATP content, which eventually led to endothelial dysfunction and cell death. In summary, exposure to cadmium caused endothelial dysfunction by disrupting lipid metabolism in HMEC‐1. These changes were mainly due to FFA accumulation and FAO inhibition, which further induced ROS generation and mitochondrial dysfunction. Moreover, our results provide novel insight into understanding the alterations of lipid metabolism induced by Cd exposure in ECs. Abstract : Cadmium is an environmental pollutant that seriously affects human health. This type of exposure can significantly increase the prevalence of dyslipidemia. Besides, it is an independent factor of cardiovascular disease, and endothelium is one of the important target organs. Therefore, the research involving whether the exposure of cadmium can interfere with the lipid metabolism of endothelial cells is crucial. And the novel phenomenon and its possible mechanism have been demonstrated in the work.